Systemic treatment of the metastatic renal cell carcinoma: usefulness of the apparent diffusion coefficient of diffusion-weighted MRI in prediction of early therapeutic response - Mytsyk, Yulian; Pasichnyk, Serhiy; Dutka, Ihor; Dats, Ihor; Vorobets, Dmytro; Skrzypczyk, Michał; Uteuliyev, Yerzhan; Botikova, Andrea; Gazdikova, Katarina; Kubatka, Peter; Urdzik, Peter; Kruzliak, Peter (Clinical and experimental medicine, 2020)
Accurate prediction of early treatment response to systemic therapy (ST) with tyrosine kinase inhibitors (TKI) in patients with metastatic renal cell carcinoma (mRCC) could help avoid ineffective and expensive treatment with serious side effects. Neither RECIST v.1.1 nor Choi criteria successfully discriminate between patients with mRCC who received ST having a short or long time to progression (TTP). There is no biomarker, which is able to predict early therapeutic response to TKIs application in patients with mRCC. The goal of our study was to investigate the potential of apparent diffusion coefficient (ADC) of diffusion-weighted imaging (DWI) of MRI in prediction of early therapeutic response to ST with pazopanib in patients with mRCC. The retrospective study enrolled 32 adult patients with conventional mRCC who received pazopanib (mean duration-7.5 ± 3.45). The mean duration of follow-up was 11.85 ± 4.34 months. In all patients as baseline examination and 1 month after treatment, 1.5T MRI including DWI sequence was performed followed by ADC measurement of the main renal lesion. For assessment of the therapeutic response, RECIST 1.1 is used. Partial response (PR), stable disease (SD) and progressive disease (PD) were observed in 12 (37.50%), 10 (31.25%) and 10 (31.25%) cases with mean TTP of 10.33 ± 2.06 months (95% confidence interval, CI = 9.05-11.61), 7.40 ± 2.50 months (95% CI = 5.61-9.19) and 4.20 ± 1.99 months (95% CI = 2.78-5.62) accordingly (p < 0.05). There was no difference in change of main lesions' longest size 1 month after ST in patients with PR, SD and PD. Comparison of mean ADC values before and 1 month after systemic treatment showed significant decrease by 19.11 ± 10.64% (95% CI = 12.35-25.87) and by 7.66 ± 6.72% (95% CI = 2.86-12.47) in subgroups with PR and SD, respectively (p < 0.05). There was shorter TTP in patients with mRCC if ADC of the main renal lesion 1 month after the ST increased from the baseline less than 1.73% compared to patients with ADC levels above this threshold: 5.29 ± 3.45 versus 9.50 ± 2.04 months accordingly (p < 0.001). Overall, our findings highlighted the use of ADC as a predictive biomarker for early therapeutic response assessment. Use of ADC will be effective and useful for reliable prediction of responders and non-responders to systemic treatment with pazopanib.
Keywords: ROC Curve; ledviny; sulfonamidy; Diffusion Magnetic Resonance Imaging; karcinom z renálních buněk; Renal cell carcinoma; Sulfonamides; Kaplan-Meier Estimate; Progress; Tyrosine kinase inhibitor; Diffusion-weighted imaging; Apparent diffusion coefficient; Prediction; lidé středního věku; difuzní magnetická rezonance; výsledek terapie; indazoly; Angiogenesis Inhibitors; ženské pohlaví; Kaplanův-Meierův odhad; retrospektivní studie; Targeted therapy; lidé; inhibitory angiogeneze; Pyrimidines; MRI; mužské pohlaví; senioři; Healthy Volunteers; Systemic treatment; Kidney Neoplasms; Treatment Outcome; Aged; Retrospective Studies; Humans; Carcinoma, Renal Cell; Early response; nádory ledvin; zdraví dobrovolníci pro lékařské studie; Female; Imaging biomarker; ROC křivka; Indazoles; Middle Aged; Male; Kidney; pyrimidiny